(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Due to its beneficial impact on language learning, the use of songs in language instruction, especially for younger students, has drawn a lot of attention. Songs offer an entertaining and captivating way to teach English, motivating young students to take an active role in their education. Songs’ rhythm and melody aid in strengthening listening comprehension, pronunciation, and word recall. Additionally, songs frequently include recurring structures that help kids learn new language patterns and syntax. This article discusses the impact of songs on teaching vocabulary to young learners. It explores how incorporating songs into vocabulary lessons can enhance language acquisition, improve memory retention, and make learning more enjoyable and effective for young students. Songs offer a fun and engaging way to reinforce new words and phrases, fostering both language development and motivation.